Antibacterial and molecular docking studies of newly synthesized nucleosides and Schiff bases derived from sulfadimidines - Hamada H. Amer (Nature Portfolio, 2021)
Abstract A new series of nucleosides, moieties, and Schiff bases were synthesized from sulfadimidine. Infrared (IR), 1HNMR, 13C NMR, and mass spectrometry techniques and elemental analysis were employed to elucidate the synthesized compounds. The prepared analogues were purified by different chromatographic techniques (preparative TLC and column chromatography). Molecular docking studies of synthesized compounds 3a, 4b, 6a, and 6e demonstrated the binding mode involved in the active site of DNA gyrase. Finally, all synthesized compounds were tested against selected bacterial strains. The most effective synthesized compounds against S. aureus were 3a, 4d, 4b, 3b, 3c, 4c, and 6f, which exhibited inhibition zones of inhibition of 24.33 ± 1.528, 24.67 ± 0.577, 23.67 ± 0.577, 22.33 ± 1.528, 18.67 ± 1.528 and 19.33 ± 0.577, respectively. Notably, the smallest zones were observed for 4a, 6d, 6e and 6g (6.33 ± 1.528, 11.33 ± 1.528, 11.67 ± 1.528 and 14.66 ± 1.155, respectively). Finally, 6b and 6c gave negative zone values. K. pneumoniae was treated with the same compounds and the following results were obtained. The most effective compounds were 4d, 4c, 4b and 3c, which showed inhibition zones of 29.67 ± 1.528, 24.67 ± 0.577, 23.67 ± 1.155 and 19.33 ± 1.528, respectively, followed by 4a and 3d (15.33 ± 1.528 for both), while moderate results (13.67 ± 1.155 and 11.33 ± 1.528) were obtained for 6f and 6g, respectively. Finally, 6a, 6b, 6c, 3a, and 3b did not show any inhibition. The most effective compounds observed for the treatment of E. coli were 4d, 4b, 4c, 3d, 6e and 6f (inhibition zones of 26.33 ± 0.577, 21.67 ± 1.528, 21.67 ± 1.528, 19.67 ± 1.528, 17.67 ± 1.155 and 16.67 ± 1.155, respectively). Compounds 3b, 3c, 6a, 6c, and 6g gave moderate results (13.67 ± 1.528, 12.67 ± 1.528, 11.33 ± 0.577, 15.33 ± 1.528 and 12.67 ± 1.528, respectively), while 6b showed no effect. The MIC values against S. aureus ranged from 50 to 3.125 mg, while those against E. coli and K. pneumoniae ranged from 50 to 1562 mg. In vitro, the antibacterial effects were promising. Further research is required to study the in vivo antibacterial effects of these compounds and determine therapeutic doses.